Vandalizing the Commons - Pavoni, A. (2022)
The chapter is based in Bologna, Italy, and focuses on an (in)famous event that took place in the city in March 2016, when the renowned street artist Blu took the drastic decision to erase all his murals from the city’s walls. Prior to this event, various graffiti, included some by Blu, had been removed from the city’s walls to populate the exhibition ‘Street Art. Banksy & Co.’ Taking inspiration from Blu’s iconoclastic protest, the chapter develops a theoretical discussion that intersects notions of art, heritage and vandalism, exploring the contemporary obsession with physical preservation and the way it surreptitiously seeped through the lively public debate that followed Blu’s decision to erase his murals. Pointing towards a notion of urban commons that is dynamic, conflictual and in becoming, the chapter shows the potential of Blu’s gesture in the context of the ongoing co-optation of street art and, more generally, vis-à-vis the complex relation between street politics, public art and urban commons.